The impact of using thermal insulation and solar energy on the reduction of energy consumption, case of housing in Constantine, Algeria - BENSEHLA Sofiane; LAZRI Youcef (Universty Of El-oued جامعة الوادي, 2019)
The purpose of this document is to optimize integrated solutions to the envelope of a building and to combine solar energy with architecture to achieve an optimal level of energy consumption in a collective dwelling. This is done by using materials performance in thermal insulation such as cork, polystyrene, brick, renewable energy, an architectural form that must take into account solar radiation in summer and winter. The objective is to evaluate the evolution of the energy needs according to the energy efficiency measures (BBC case) and the thermal comfort conditions, with geographical coordinates of the basic building correspond to the city of Constantine, in Algeria. The use of the TRNSYS version 16 software was chosen to make the comparison simulations between the two collective dwellings in the city of Constantine. The first is that of a current housing standard case of the city, and the second housing is the optimizing one proposed as project in Constantine city. For a positive and efficient return , where the final goal is to examine the effectiveness of the first compared to the second in terms of energy, economic and environmental.
Intervention
Keywords: Optimize; BBC; Energy; Constantine; Collective-dwellings.